Modification of the Outer Cam of Sprags and Performance Analysis of Sprag Clutches - Liu Yinwei; Li Zhengminqing; Zhao Jiang; Leng Junjie (Jixie chuandong)
A method for modifying the outer cam of sprags is proposed, the calculation method of the force of sprags in the overrunning and the engagement condition is studied, and the influence of different modification curves on the contact performance of sprags is analyzed. The results show that the modification of the outer cam of sprags can reduce the contact stress of the sprag clutch wedge in the overrunning condition without affecting the engagement performance, which is helpful to reduce the overrunning wear of sprags.